Mangrove community structure survey in Pedada Bay, Ajuy, Iloilo. - Bravo, Mark Gonzaludo (2004.)
Mangroves are uniquely tropical, globally occuring and one of the most pervasive coastline ecosystems. They are one of the highly productive and one of the most diverse wetlands on earth. The objective of this study is to assess the community structure of mangroves in Pedada Bay, Ajuy, in particular the species composition and diversity in relation to the physical and chemical factors. Pedada Bay is located in the northern part of Panay Island. The transect line plot method was used to survey the community structure of the mangroves. The floristic composition of Pedada Bay was composed of a total of 18 true mangrove species belonging to 11 families. The true mangroves were Family Avicenniaceae represented by Avicennia marina and A. rumphiana, Family Bombacaceae represented by Compostemon philippinensis, Family Combrataceae represented by Lumnitzera racemosa, Family Euphorbiaceae represented by Exoecaria agallocha, Family Meliaceae composed of Xylocarpus granatum and X. moluccensis, Family Myrsinaceae composed of Aegiceras corniculatum and A. floridum, Family Myrtaceae represented by Osbornia octodonta, Family palmae represented by Nypa fruticans, Family Rhizophoraceae composed of Bruguiera cylindrica, Ceriops decandra, Rhizophora apiculata, R. mucromata, and R. stylosa, Family Rubiaceae composed of Scyphiphora hydrophyllacea, and Family sonneratiaceae composed of Sonneratia alba. Average basal area for the entire Pedada Bay ranges from 300.564 msquared/ha for Sonneratia alba to 0.008 msquared/ha for Rhizophora mucromata. Average stems per hectare ranges from 1,988 for Avicennia marina to 5 stems per hectare for Aegiceras corniculatum. Of the three barangays of Pedada Bay, Barangay Pedada had the highest basal area. Sonneratia alba was the most dominant species in the bay. Avicennia marina was densest, the most frequently occuring, and the most important species in Pedada Bay. The entire area had a high diversity index of 0.718. A distinct zonation pattern was observed in the area. Seedling density ranges from 1,421 seedlings for Sonneratia alba to 1 seedling for Scyphiphora hydrophyllacea. Sapling density ranges from 166 for Avicennia marina to 1 for Scyphiphora hydrophyllacea.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Mangroves -- Pedada Bay, Ajuy, Iloilo